2006
DOI: 10.1038/sj.mp.4001921
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous glucocorticoids protect against TNF-alpha-induced increases in anxiety-like behavior in virally infected mice

Abstract: Endogenous glucocorticoids restrain proinflammatory cytokine responses to immune challenges such as viral infection. In addition, proinflammatory cytokines induce behavioral alterations including changes in locomotor/exploratory activity. Accordingly, we examined proinflammatory cytokines and open-field behavior in virally infected mice rendered glucocorticoid deficient by adrenalectomy (ADX). Mice were infected with murine cytomegalovirus (MCMV), and open-field behavior (36 h post-infection) and plasma concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 64 publications
3
27
1
Order By: Relevance
“…For example, transgenic mouse lines deficient in central signaling involving pro-inflammtaory cytokines, such as interleukin-1β (IL-1β) or tumor necrosis factor-α (TNF-α), consistently exhibit altered anxiety behavior in the elevated plus maze or open field test. (Silverman, Macdougall et al 2007;Koo and Duman 2009). Further, an infusion of IL-1β into the lateral ventricle is sufficient to induce anxiety like behavior in the elevated plus maze (Koo and Duman 2009).…”
Section: Introductionmentioning
confidence: 98%
“…For example, transgenic mouse lines deficient in central signaling involving pro-inflammtaory cytokines, such as interleukin-1β (IL-1β) or tumor necrosis factor-α (TNF-α), consistently exhibit altered anxiety behavior in the elevated plus maze or open field test. (Silverman, Macdougall et al 2007;Koo and Duman 2009). Further, an infusion of IL-1β into the lateral ventricle is sufficient to induce anxiety like behavior in the elevated plus maze (Koo and Duman 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Benzodiazepines that bind to the GABA A receptor have been widely used clinically to treat anxiety, and mice deficient in GAD65 show increased anxiety-like behavior (Aihara et al ., 1994). Several cytokines and chemokines, including interferon α, C-C motif ligand 2 (CCL2, or MCP-1), and tumor necrosis factor α (TNF), are known to increase anxiety behavior ( Fahey et al ., 2007; Silverman et al ., 2007; Breese et al ., 2008). IL2 also appears to be an inducer of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…These cells release a range of chemokines and cytokines which allow for bidirectional communication between the brain and immune system. There is now very good evidence to suggest that cytokines directly modulate HPA axis activity (Dunn, 2000;Jara et al, 2006;Mastorakos and Ilias, 2006;Mulla and Buckingham, 1999;Rivest, 2001;Savastano et al, 1994;Torpy and Chrousos, 1996;Turnbull and Rivier, 1999), anxiety-and depression-related behaviour (Anisman and Merali, 1999;Breese et al, 2008;Connor and Leonard, 1998;Craddock and Thomas, 2006;Leonard, 2001;Leonard, 2006;Nautiyal et al, 2008;O'Brien et al, 2004;Schiepers et al, 2005;Silverman et al, 2007;Wichers and Maes, 2002) and pain (McMahon et al, 2005;Moalem and Tracey, 2006;Sommer and Kress, 2004;Thacker et al, 2007;Watkins et al, 2003;Wieseler-Frank et al, 2005a;Wieseler-Frank et al, 2005b). Our recent work (Roche et al, 2006;Roche et al, 2008), and that of others (Croci et al, 2003;Panikashvili et al, 2001;Smith et al, 2000;Smith et al, 2001a;Smith et al, 2001b), has demonstrated a role for the endocannabinoid system in regulating peripheral and brain cytokine responses to immune challenge/stress in vivo.…”
Section: Stress-induced Analgesiamentioning
confidence: 99%